Banana starch: production, physicochemical properties, and digestibility-a review - Zhang, P.; Whistler, R.L.; Bemiller, J.N.; Hamaker, B.R.
The large quantity of green cull bananas has the potential of being used industrially and, thereby, to improve banana economics and eliminate the large environmental problem presented by banana waste. This review summarizes the present knowledge of the composition, structure, physiochemical properties, modifications, and digestibility of banana starches and provides suggestions for needed research to improve the utilization of green cull bananas.
Keywords: BANANA; STARCH; STRUCTURE; PHYSICOCHEMICAL PROPERTIES; MODIFICATIONS; DIGESTIBILITY